Local Community Participation in Tourism Development at Munduk Tourism Village, Bali - Putu Sekar Kinaryaning Langit; Yayu Indrawati; Ni Putu Ratna Sari (Cita Konsultindo Research Center, 2024)
This study looks at the tourism development in Bali's Munduk Tourism Village and emphasizes the value of community involvement. In Indonesia, tourism is a key driver of economic growth and the government is concentrating on sustainable tourism development to guarantee long-term gains. Munduk Village, which provides a comprehensive view of the surrounding landscape and culture, received recognition as an independent tourism attraction in 2014 and the Indonesian Tourism Village Award in 2022. Through community involvement in management and environmental conservation, this village promotes a tourism. Observation, interviews, and literature reviews were used in conjunction with a qualitative descriptive method to perform this study from December 2023 to April 2024. Munduk Village has experienced a number of phases in the tourism area's life cycle, from discovery to local communities' involvement in tourism development, according to the study's findings. The village government, customary government, Village Tourism Development Agency, tourism awareness group, and other local organizations all play a part in the local community's involvement. In addition to actively participating in the development, management, and promotion of tourism, local communities also profit monetarily from it. In conclusion, all forms of local community participation have a big contribution to the development of the tourism sector in Munduk Tourism Village.